Scientific Explanation Sebagai Kerangka Konseptual Pembelajaran Permasalahan Sosial Di SMP - Tri Gunawan; Sudrajat Sudrajat; Trapsila Siwi Hutami (STKIP Singkawang, 2026)
This article examines the conceptual and pedagogical contribution of scientific explanation, rooted in philosophy of science, to the teaching of social issues in junior high school social studies. Although social studies aims to develop critical and analytical thinking, classroom practices often remain descriptive and less focused on explaining causal mechanisms behind social phenomena. This study employs a narrative literature review drawing from key works in philosophy of science and recent educational research on explanation and argumentation. The analysis indicates that models of scientific explanation, particularly causal reasoning and contextual explanation, provide a structured framework for helping students analyze social problems beyond factual description. Pedagogically, integrating scientific explanation principles supports evidence-based discussion, structured reasoning, and scaffolded explanation practices in social studies classrooms. The study concludes that adopting scientific explanation as a conceptual framework can strengthen students’ critical thinking and socio-scientific literacy in learning social issues at the junior high school level.